Immunohistochemical Analysis of p53 Protein and Proliferating Cell Markers (PCNA and Ki 67) in Very Well Differentiated Adenocarcinoma of the Stomach - Ayşe DURSUN; Dardo CENTURION; lsamu KINO; Yasuhisa NAITO (Turkish Journal of Gastroenterology, 2020)
-